Meningkatkan Motivasi dan Hasil Belajar Matematika Siswa melalui Model Pembelajaran Kooperatif Tipe Teams Games Tournament - Miftahul Janna; Majid Majid; Bertu Rianto Takaendengan (Department of Mathematics, Universitas Negeri Gorontalo, 2026)
This study is a classroom action research aimed at improving students’ motivation and mathematics learning outcomes through the implementation of the cooperative learning model, Teams Games Tournament (TGT), on the topic of quadratic equations. The research subjects were 16 ninth-grade students of MTs Al-Mabrur Bone Raya. The study was conducted in two cycles, each consisting of the stages of planning, action implementation, observation, and reflection. Data collection techniques included observation, questionnaires, and achievement tests. The data were analyzed using both quantitative and qualitative descriptive methods. The results indicate that the application of the TGT model enhanced students’ motivation and mathematics learning outcomes. In Cycle I, 75% of students demonstrated high or very high learning motivation, with cognitive learning outcomes at 62.5%, affective at 76%, and psychomotor at 66%. Following improvements in Cycle II, learning motivation increased to 93.75%, cognitive achievement reached 81.25%, and affective and psychomotor scores both rose to 88%. Students also showed greater participation in discussions, increased willingness to ask questions, and improved accuracy in problem-solving. Therefore, the TGT cooperative learning model is effective in enhancing students’ motivation and learning outcomes in mathematics, while also fostering the development of positive skills and attitudes throughout the learning process.